Realization and measurement of Airy transform of Gaussian vortex beams. (November 2021) - Zhou, Lu; Zhou, Tong; Wang, Fei; Li, Xia; Chen, Ruipin; Zhou, Yimin; Zhou, Guoquan
Highlights: The beam propagation factor of the transformed Gaussian vortex beam is derived. The phase information of the transformed Gaussian vortex beam is first measured. The effect of the topological charge on the Airy transform is analyzed. The topological charge is conserved in the Airy transformation. The properties of Airy transform of vortex beams are well demonstrated. Abstract: Airy transformation is a useful technique to modulate amplitude and phase of a light beam, which has important applications in particle trapping/manipulation, optical communications and optical imaging. However, most of the studies only focused on the Airy transform of Gaussian beams and other vortex-free beams in the past. In this paper, the Airy transform of Gaussian vortex beams, which are the most common vortex beams, is investigated. A universal analytical expression of the Gaussian vortex beams with topological charge (TC) m passing through an Airy transform optical system is derived. We carry out a detailed study on the output beams' characteristics after the Airy transform of the Gaussian vortex beams with m = ± 1 and ± 2. The analytical expressions for the centroid, the beam spot size, the divergence angle and the beam propagation factor of the output beams are derived. The effects of the Airy control parameters and the TC on the normalized intensity distribution, the phase distribution, the centroid, the beam spot size and the beam propagation factor of the output beams are investigated both theoretically and experimentally. The experimental results agree reasonably well with the theoretical results which illustrate the properties of Airy transform of the Gaussian vortex beams.